2008
DOI: 10.1186/1472-698x-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of health effects of cooking smoke among women in the Gondar Region of Ethiopia: a pilot survey

Abstract: Background: The burning of biomass fuels results in exposure to high levels of indoor air pollution, with consequent health effects. Possible interventions to reduce the exposure include changing cooking practices and introduction of smoke-free stoves supported by health education. Social, cultural and financial constraints are major challenges to implementation and success of interventions. The objective of this study is to determine awareness of women in Gondar, Ethiopia to the harmful health effects of cook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 9 publications
3
27
0
Order By: Relevance
“…Due to the small number of measurements conducted, conclusions presented here are perhaps anecdotal. Yet exposure campaigns, as a first step to addressing health hazards, can result in significant behavior change due to increased community awareness of the problem (Diaz et al 2008;Edelstein et al 2008;Madajewicz et al 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the small number of measurements conducted, conclusions presented here are perhaps anecdotal. Yet exposure campaigns, as a first step to addressing health hazards, can result in significant behavior change due to increased community awareness of the problem (Diaz et al 2008;Edelstein et al 2008;Madajewicz et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Four households and one secondary school were selected. Choice of cooking fuel often correlates with a household's socio-economic status (Edelstein et al 2008;Smith 2002). Thus, on a small scale, these sites also represent the socioeconomic demographic within the region.…”
Section: Sampling Layoutmentioning
confidence: 99%
“…In addition the majority of respondents were aware and agreed that cooking with biomass fuel had a negative effect on their children's health ( Table 3). The studies by Edelstein et al [30] and Osagbemi et al [31] had also shown considerable awareness of ill health effects of biomass fuel use in their studied communities. It is of note that a considerable proportion placed wood as the best fuel along with natural gas and LPG.…”
Section: Awareness Of Health Impacts Of Cooking Fuelsmentioning
confidence: 88%
“…The burning of this form of energy results in the release of hundreds of toxic air pollutants that have been associated with an increased risk of developing respiratory illnesses c 2010 Blackwell Publishing Ltd, Clinical & Experimental Allergy, 40 : 1719-1731 [141][142][143]159]. With respect to prenatal exposure, biomass fuel use has been associated with low birth weight, intrauterine growth restriction and preterm parturition [144,[160][161][162].…”
Section: Air Pollutionmentioning
confidence: 99%